Assessment of colorectal cancer molecular features along bowel subsites challenges the conception of distinct dichotomy of proximal versus distal colorectum. Issue 6 (17th March 2012) - Yamauchi, Mai; Morikawa, Teppei; Kuchiba, Aya; Imamura, Yu; Qian, Zhi Rong; Nishihara, Reiko; Liao, Xiaoyun; Waldron, Levi; Hoshida, Yujin; Huttenhower, Curtis; Chan, Andrew T; Giovannucci, Edward; et al.
Abstract : Objective: Colorectal cancer is typically classified into proximal colon, distal colon and rectal cancer. Tumour genetic and epigenetic features differ by tumour location. Considering a possible role of bowel contents (including microbiome) in carcinogenesis, this study hypothesised that tumour molecular features might gradually change along bowel subsites, rather than change abruptly at splenic flexure. Design: Utilising 1443 colorectal cancers in two US nationwide prospective cohort studies, the frequencies of molecular features (CpG island methylator phenotype (CIMP), microsatellite instability (MSI), LINE-1 methylation and BRAF, KRAS and PIK3CA mutations) were examined along bowel subsites (rectum, rectosigmoid junction, sigmoid, descending colon, splenic flexure, transverse colon, hepatic flexure, ascending colon and caecum). The linearity and non-linearity of molecular relations along subsites were statistically tested by multivariate logistic or linear regression analysis. Results: The frequencies of CIMP-high, MSI-high and BRAF mutations gradually increased from the rectum (<2.3%) to ascending colon (36–40%), followed by falls in the caecum (12–22%). By linearity tests, these molecular relations were significantly linear from rectum to ascending colon (p<0.0001), and there was little evidence of non-linearity (p>0.09). Caecal cancers exhibited the highest frequency of KRAS mutations (52% vs 27–35% in other sites; p<0.0001). Conclusions: The frequencies of CIMP-high, MSI-high and BRAF mutations in cancer increased gradually along colorectum subsites from the rectum to ascending colon. These novel data challenge the common conception of discrete molecular features of proximal versus distal colorectal cancers, and have a substantial impact on clinical, translational and epidemiology research, which has typically been performed with the dichotomous classification of proximal versus distal tumours.